Implementasi Media Pembelajaran Interaktif Fisika Berbasis Aplikasi Android Dengan MIT App Inventor - Vijen Vigel Koroh; Rolles Nixon Palilingan; Jeferson Polii; Jimmy Lolowang (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This research aims to create or design an interactive physics learning media application using MIT App Inventor on GLB and GLBB topics. This research applies the MDLC (Multimedia Development Life Circle) method by Luther-Sutopo in the application creation process. The following stages in MDLC are concept, design, material collecting, assembly, testing, and distribution. The Android application created was tested using two stages in MDLC, namely the alpha validator and beta validator, where the alpha validator consisted of material experts and media experts. In contrast, the beta validator comprised 14 students majoring in first-semester physics education. The analytical approach used is a qualitative method and a quantitative method to assess how appropriate the learning media created is. The research shows the results, namely a) Creation of interactive physics learning media based on Android applications using MIT App Inventor on GLB and GLBB topics, b) The level of feasibility of interactive physics learning applications based on Android applications based on media experts, namely 91% or very feasible, and based on material experts. Namely 90.6% or very feasible, and c) Based on the implementation and results of trials with students, the level of feasibility of the Android-based physics interactive learning application is 84.46% or worthy of being an alternative reference source for physics learning on GLB and GLBB topics.